Comparative Analysis of the Legal System in the Republic of Indonesia and Malaysia: Case Studies on Corruption Crimes: Analisis Perbandingan Sistem Hukum di Negara Republik Indonesia dan Negara Malaysia: Studi Kasus tentang Tindak Pidana Korupsi - Altamis, Muhammad Iqbal (UPMI Proceeding Series, 2023)
This research aims to conduct a comparative analysis between the legal systems in the Republic of Indonesia and Malaysia in the context of handling corruption crimes. Corruption is a serious issue that harms both the state and society, thus making it important to study the legal approaches used in addressing corruption cases in both countries.This study employs a legal comparative method to analyze the differences and similarities within the legal systems of both countries. The main focus of this analysis includes aspects such as the definition and classification of corruption crimes, the law enforcement agencies responsible, the prosecution process, and the penalties imposed on the perpetrators of corruption. The data and information used in this research are derived from various legal sources, including legislation, court decisions, and relevant legal literature.The findings of this research are expected to provide a deeper understanding of the differences and similarities within the legal systems of both countries, as well as to highlight the strengths and weaknesses of each legal system in combating corruption. With a better understanding of effective legal systems, both countries can learn from each other and enhance their law enforcement efforts in combating corruption.